Seeking simplicity, navigating complexity: How veterinarians select an antimicrobial drug, dose, and duration for companion animals - Scarborough, Ri O.; Bailey, Kirsten E.; Sri, Anna Ellen; Browning, Glenn Francis; Hardefeldt, Laura Y. (Journal of veterinary internal medicine, 2024)
Background Minimizing harm from antimicrobials requires use of the narrowest spectrum drug, at an effective dose for the minimum effective duration. Many prescribers are not currently following these guidelines. To address suboptimal antimicrobial use, the underlying reasons must be understood. Objectives To identify factors influencing choices of antimicrobial drug, dose, and duration for companion animals. Subjects Twenty‐two veterinarians treating companion animals in Australia. Diversity of participants was deliberately sought. Methods Semistructured interviews were conducted online. Two case studies were discussed, and then a range of broader questions was posed. Transcripts were analyzed thematically, using an inductive approach. Results Few participants chose guideline‐concordant management for the case studies. Prescribing choices were influenced by a complex array of factors associated with the clinical case, pet owner, drug, veterinarian, veterinary colleagues, and external factors. Key factors driving broad‐spectrum antimicrobial use included a sense of safety, habit, ease of administering the drug (especially in cats), pharmaceutical marketing, and the self‐perpetuating dispensary cycle. Many participants were concerned about antimicrobial resistance, but insufficiently informed about how to minimize this risk. Several participants believed that longer duration of treatment and ensuring patients finish a predetermined course would decrease the risk of antimicrobial resistance and improve clinical outcomes. Conclusions and Clinical Importance Veterinarians are engaged with the concept of antimicrobial stewardship, but face numerous practical barriers and require more information. In particular, improved education is needed on enhancing patient safety by minimizing both spectrum of activity and duration of treatment, and dispelling myths about “finishing the course.”